Fortune and Misfortune of Italian Chivalric Literature in the Early Modern Poland - Pietrzak-Thėbault, Joanna (Załącznik Kulturoznawczy, 2023)
Two masterpieces of the chivalric epic literature, Orlando Furioso of Lodovico Ariosto and Gerusalemme Liberata of Torquato Tasso have had their Polish versions of rare beauty and value thanks to the translator of genius, Piotr Kochanowski. The fate of their reception is, however, very different. The reasons of the absence of Orlando Furioso remain still inexplicable, while the number and diversity of the editions of its original version in Polish libraries could prove the contrary. Anyway, only detailed provenance research would establish the real origin of these books. The evolution of the reception of the Gerusalemme Liberata during the whole 17th c. is an interesting example of a fusion of both foreign and domestic motifs, and of an attractiveness of the Renaissance patterns in the new times